2021
DOI: 10.3390/met11050777
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Correlation between Initial Microstructure and Critical Current Density of Nb-46.5 wt%Ti Superconducting Material

Abstract: We have investigated the effect of initial microstructures on the change in critical current density (Jc) of Nb-46.5 wt%Ti (NbTi) superconducting material. It is well known that α-Ti phases distributed in NbTi material act as a flux pinning center, resulting in an improvement in critical current density. Therefore, it is crucial to obtain the grain-refined microstructure, which is strongly related with precipitation of uniformly distributed fine α-Ti phases and higher volume faction of α-Ti phases, as α-Ti pha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 33 publications
(48 reference statements)
0
2
0
Order By: Relevance
“…Boenisch et al [ 29 ] investigated the thermal stability of NbTi alloys in a wide concentration range. Moon et al [ 30 ] and Kim et al [ 31 ] showed the relationship between the initial structure and the critical current density, while other authors observed changes in the microstructure due to various external influences [ 2 , 6 , [32] , [33] , [34] ]. Storozhilov et al [ 35 ] investigated the effect of severe plastic deformation on the decomposition of supersaturated solid solution in Nb–48.5 wt % Ti.…”
Section: Introductionmentioning
confidence: 99%
“…Boenisch et al [ 29 ] investigated the thermal stability of NbTi alloys in a wide concentration range. Moon et al [ 30 ] and Kim et al [ 31 ] showed the relationship between the initial structure and the critical current density, while other authors observed changes in the microstructure due to various external influences [ 2 , 6 , [32] , [33] , [34] ]. Storozhilov et al [ 35 ] investigated the effect of severe plastic deformation on the decomposition of supersaturated solid solution in Nb–48.5 wt % Ti.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, they are many different superconducting materials, e.g., high-temperature superconductors [ 1 ], including iron-based superconductors [ 2 ], NbTi [ 3 ], and Nb 3 Sn [ 4 ]. However, now, it seems that the MgB 2 material is the most promising one for the production of coils because it consists of cheap components (low price of wires) and is characterized by high critical temperature (39 K liquid hydrogen, cryocooler), low anisotropy (wires made using the powder-in-a-tube method), and high upper critical field [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%